Starch granules
Starch granules with added polysaccharides and lubricants improve handling and dispersibility in resin compositions, addressing productivity and dispersibility issues, resulting in enhanced mechanical performance and cost-effective production.
Patent Information
- Application Number
- JP2020186464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-11-09
AI Technical Summary
Existing methods for producing starch-containing resin compositions face challenges with the low productivity and poor dispersibility of powdered starch due to its small bulk density and strong self-cohesive force, making it difficult to handle and disperse effectively in resin matrices.
The incorporation of starch granules containing starch, a water-soluble polysaccharide, and a starch lubricant, such as surfactants or starch plasticizers, with specific content ratios, along with a semi-wet granulation process, enhances the handling, dispersibility, and productivity of starch in resin compositions.
The starch granules exhibit improved handleability, productivity, and dispersibility in thermoplastic resin compositions, reducing environmental pollution, enhancing mechanical performance, and moldability while lowering production costs.
Smart Images

Figure 0007605617000005 
Figure 0007605617000006 
Figure 0007605617000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a starch granule. [Background technology]
[0002] In recent years, many compositions have been proposed in which organic or inorganic fillers are mixed with biodegradable resins or thermoplastic resins. Among these fillers, "starch" is a relatively inexpensive organic filler, and thermoplastic resins containing starch as an extender, a bio-degree improver, or a biodegradation promoter for the biodegradable resins or thermoplastic resins (hereinafter also referred to as starch-containing resin compositions) have attracted attention. Patent documents 1 to 4 propose resin compositions containing thermoplastic resins and starch, but when powdered starch is supplied to a melt kneading device (a representative example of which is an extruder) and melt-blended to obtain a composition, the starch is a powder with a low bulk density, so it is not easy to supply it to the melt kneading device, and the productivity of the starch-containing resin composition is extremely low. In addition, the starch-containing resin composition has a problem that it is not easy to disperse starch well in a resin matrix due to the strong self-aggregation force of starch. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-120651 A [Patent Document 2] Patent No. 3477440 [Patent Document 3] Patent No. 4364435 [Patent Document 4] Patent No. 2961135 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a starch granule that is excellent in terms of handleability of the starch granule, productivity of the starch granule, versatility of applicable resins, dispersibility of starch in a thermoplastic resin composition, etc. [Means for solving the problem]
[0005] The starch granules of the present invention contain starch, a water-soluble polysaccharide, and a starch lubricant, the starch lubricant being at least one selected from the group consisting of surfactants and starch plasticizers, the content of the water-soluble polysaccharide being 0.1 to 10 parts by weight per 100 parts by weight of starch, and the content of the starch lubricant being 0.1 to 10 parts by weight per 100 parts by weight of starch. In one embodiment, the content of the water-soluble polysaccharide is 0.1 to 5 parts by weight relative to 100 parts by weight of starch, and the content of the starch lubricant is 0.1 to 5 parts by weight relative to 100 parts by weight of starch. In one embodiment, the content of the water-soluble polysaccharide is 0.1 to 3 parts by weight relative to 100 parts by weight of starch, and the content of the starch lubricant is 0.1 to 3 parts by weight relative to 100 parts by weight of starch. In one embodiment, the water-soluble polysaccharide is at least one selected from the group consisting of pullulan and dextrin. In one embodiment, the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerin fatty acid esters, and alcohol esters of condensed hydroxy fatty acids. In one embodiment, the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin, and sorbitol. In one embodiment, the starch is pregelatinized starch. In one embodiment, the starch granules have a moisture content of 1% by weight to 30% by weight. According to another aspect of the present invention, there is provided a method for producing a starch granule, comprising a mixing step of mixing starch, a water-soluble polysaccharide, and a starch lubricant, and a granulation step of granulating the mixture obtained through the mixing step. In one embodiment, the mixing step further comprises mixing water, and the amount of water is 5 parts by weight to 20 parts by weight per 1 part by weight of the water-soluble polysaccharide. In one embodiment, the granulation step includes granulation by a semi-wet granulation method. In one embodiment, the granulation step includes granulation by a disk pelletizer method. Effect of the Invention
[0006] According to the present invention, it is possible to provide a starch granule that is excellent in terms of handleability of the starch granule, productivity of the starch granule, versatility of applicable resins, dispersibility of starch in a thermoplastic resin composition, etc. [Brief description of the drawings]
[0007] [Figure 1] 1 is a photograph showing the appearance of the starch granules obtained in Example 1. [Diagram 2] 1 is an appearance photograph showing the evaluation results of Example 10 (dispersibility of starch in a resin composition). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] A. Overview of starch granules The starch granules of the present invention contain starch, a water-soluble polysaccharide, and a starch lubricant. The starch lubricant is at least one selected from the group consisting of surfactants and starch plasticizers. The content of the water-soluble polysaccharide is 0.1 to 10 parts by weight relative to 100 parts by weight of the starch. The content of the starch lubricant is 0.1 to 10 parts by weight relative to 100 parts by weight of the starch.
[0009] The starch granules of the present invention are used in the production of a starch-containing resin composition, and can be added during melt-kneading of the resin composition.
[0010] In one embodiment, the starch granules can be obtained by processing a mixture containing starch, a water-soluble polysaccharide dissolved in water, and a starch lubricant by any appropriate method.
[0011] In the present invention, by adding the water-soluble polysaccharide and the starch lubricant, it is possible to obtain a starch granule that can be produced with excellent production efficiency and has excellent quality stability (shape stability, uniformity of pellet hardness, low fine powder contamination). In addition, by preparing the starch-containing resin composition using the starch granule, the productivity of the resin composition can be improved. Specifically, since the starch granule has a remarkably excellent stability when put into an apparatus such as an extruder, the productivity (compound processing speed per hour) of the starch-containing resin composition can be dramatically improved by using the starch granule. In addition, the working environment pollution caused by dust can be significantly improved, and the occupational safety and health environment of the workers can be improved. Furthermore, since the starch granule also has a function of cleaning the equipment, it is possible to significantly shorten the time required for cleaning the equipment when switching between the equipment. Furthermore, the starch-containing resin composition obtained by using the starch granule of the present invention has excellent starch dispersibility. In addition, since the starch granules of the present invention have the effect of enhancing moldability (high fluidity), the starch-containing resin composition obtainable by using the starch granules of the present invention can reduce the load on the extruder while containing starch at a high concentration, and can suppress excessive heat generation in the resin, making it possible to perform melt kneading while suppressing thermal deterioration of the resin and starch, thereby obtaining a starch-containing resin composition having excellent mechanical properties and moldability. By using the starch granules of the present invention that have such effects, it is possible to reduce the cost of producing a starch-containing resin composition as well as to improve its performance.
[0012] In one embodiment, the starch granule is produced by a semi-wet granulation method. The semi-wet granulation method makes the above-mentioned effects more pronounced.
[0013] The starch granules may be in any suitable shape. Typically, the starch granules are cylindrical (pellet-shaped).
[0014] When the starch granules are cylindrical, the diameter of the starch granules is, for example, 2 mm to 5 mm. The length (height) of the starch granules is, for example, 1 mm to 5 mm. With such a shape, it is possible to obtain a starch granule that can be preferably combined with a resin (particularly a thermoplastic resin). The diameter of the starch granules can be adjusted by the diameter of the die hole during granulation, and the length can be adjusted by the distance between the disk plate and the cutter. By adjusting the starch granules to the pellet size of the resin (particularly a thermoplastic resin) to be combined with the starch granules, the handling property is improved, and the dispersibility of the starch in the molten compound is improved.
[0015] The breaking stress of the filler granules measured with a Kiya hardness tester is preferably 0.05 kg to 10 kg, more preferably 0.5 kg to 8 kg, and even more preferably 1.0 kg to 7 kg. Within such ranges, the handling property and starch dispersibility are excellent. Here, the breaking stress refers to the average disintegration stress measured for 20 or more granules.
[0016] The water content of the starch granules may be any appropriate water content. The water content of the starch granules is preferably 30% by weight or less, more preferably 25% by weight or less. In one embodiment, the water content of the starch granules is preferably 0.1% by weight to 30% by weight, more preferably 0.5% by weight to 30% by weight, even more preferably 1% by weight to 30% by weight, particularly preferably 1% by weight to 20% by weight, and most preferably 17% by weight to 20% by weight. Within such a range, starch can easily change from a β structure to an α structure during melt-kneading of the resin composition.
[0017] The bulk density of the starch granules is preferably 0.3 g / cm 3~1.0g / cm 3 and more preferably 0.4 g / cm 3 ~0.8g / cm 3 and more preferably 0.5 g / cm 3 ~0.7g / cm 3 By increasing the bulk density, the supply rate and supply stability of the starch granules are increased when melt-kneading with a resin (especially a thermoplastic resin).
[0018] A-1. Starch As the starch, any suitable starch can be used. Typically, the starch is added in powder form. The starch can be used alone or in combination of multiple types.
[0019] In one embodiment, the starch is raw starch, for example, starch obtained from corn, potato, tapioca, sweet potato, wheat, cassava, sago, sorghum, rice, beans, kudzu, bracken, lotus, water chestnut, etc.
[0020] In another embodiment, the starch is a modified starch. Examples of modified starches include physically modified starches (e.g., gelatinized starch, fractionated amylose, moist heat treated starch, etc.), enzymatically modified starches (e.g., hydrolyzed dextrin, enzymatically decomposed dextrin, amylose, etc.), chemically decomposed modified starches (e.g., acid treated starch, hypochlorite oxidized starch, dialdehyde starch, etc.), and chemically modified starch derivatives (e.g., esterified starch, etherified starch, cationized starch, crosslinked starch, etc.).
[0021] Specific examples of the esterified starch include acetate starch, succinate starch, nitrate starch, phosphate starch, urea phosphate starch, xanthate starch, and acetoacetate starch.
[0022] Examples of the etherified starch include allyl etherified starch, methyl etherified starch, carboxymethyl etherified starch, hydroxyethyl etherified starch, and hydroxypropyl etherified starch.
[0023] Examples of the crosslinked starch include formaldehyde crosslinked starch, epichlorohydrin crosslinked starch, phosphate crosslinked starch, acrolein crosslinked starch, and the like.
[0024] The above-mentioned pregelatinized starch is a starch in which raw starch having a crystalline structure (β structure) is broken down and changed to an amorphous structure (α structure) in a temperature environment of about 70°C or higher in the presence of an appropriate amount of moisture. This change from β structure to α structure when raw starch is heated with moisture is called "gelatinization". α structure starch is preferable because it has excellent dispersibility in thermoplastic resins compared to β structure. When the above-mentioned pregelatinized starch is left at a low temperature while still containing moisture, a phenomenon in which it returns to the original β structure crystalline state (called "aging") may occur. It is known that the α structure can be maintained by quickly removing moisture from the amorphous state of pregelatinized starch. Specifically, after heating in the presence of moisture to gelatinize it, the atmosphere is reduced in a vacuum device to obtain dehydrated α structure starch. In order for β-starch to become α-starch upon heating, it is generally considered preferable for the moisture content to be 17% or more.
[0025] In one embodiment, the average primary particle size of the starch is in the range of 1 μm to 100 μm, and representative examples include corn starch 15 μm, potato 50 μm, tapioca (cassava) 20 μm, rice 5 μm, wheat 10-20 μm, sweet potato 15 μm, sago 30 μm, and mung bean 20 μm. The average primary particle size of the starch is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm. If it is in such a range, a starch granule having excellent granulation productivity can be obtained. The average particle size of starch can be obtained by morphological observation under a microscope. That is, a photograph of the powder observed under a microscope is taken, and the arithmetic average (number average) of 50 randomly selected starches is obtained.
[0026] A-2.Water-soluble polysaccharide The water-soluble polysaccharides refer to water-soluble compounds composed of long chains of monosaccharides such as glucose and mannose. In one embodiment, the water-soluble polysaccharides are water-soluble carbohydrates composed of 10 or more monosaccharides bound together. The water-soluble polysaccharides are highly hydrophilic and therefore exhibit functions such as thickening, binding, gelling, and water retention, and in the present invention, they exhibit functions such as shape stability and hardness improvement of starch granules, and water retention.
[0027] In one embodiment, the water-soluble polysaccharide may be a polymeric substance of natural origin, such as a water-soluble polysaccharide derived from a plant (seed, sap, fruit, etc.), seaweed, or microorganism.
[0028] Specific examples of the water-soluble polysaccharides include pullulan, dextrin, chitosan, tamarind seed gum, guar gum, locust bean gum, gum arabic, karaya gum, pectin, cellulose, konjac mannan, soybean polysaccharides, carrageenan, agar, tragacanth gum, alginic acid, xanthan gum, gellan gum, Agrobacterium succinoglycan, carboxymethylcellulose, cationized guar gum, etc. Among these, pullulan or dextrin is preferred, and pullulan is more preferred. The water-soluble polysaccharides may be used alone or in combination of two or more.
[0029] Dextrin is a low molecular weight carbohydrate obtained by hydrolysis of starch or glycogen. Depending on the degree of saccharification (DE) of starch, it is classified into powdered candy (DE of about 20-40), maltodextrin (DE of about 10-20), and dextrin (DE of 10 or less).
[0030] The pullulan is a polysaccharide consisting of glucose alone. Pullulan is a plant-derived microbial fermentation product made from starch, and is water-soluble and has characteristics such as water retention, thickening, lubricity, adhesion, binding, and film-forming properties. Pullulan has a thermal decomposition temperature of about 290°C and has heat resistance suitable for use in thermoplastic resins made from starch granules, making it particularly preferred.
[0031] As described above, the content of the water-soluble polysaccharide is 0.1 to 10 parts by weight relative to 100 parts by weight of the starch. The content of the water-soluble polysaccharide is preferably 0.1 to 5 parts by weight, more preferably 0.2 to 7 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the starch. Within such a range, the effects of the present invention are remarkable. In one embodiment, the content of the water-soluble polysaccharide is 0.1 to 3 parts by weight relative to 100 parts by weight of the starch.
[0032] A-3.Starch lubricants As described above, the starch lubricant is at least one selected from the group consisting of surfactants and starch plasticizers.
[0033] As described above, the content of the starch lubricant is 0.1 to 10 parts by weight relative to 100 parts by weight of the starch. The content of the starch lubricant is preferably 0.1 to 5 parts by weight, more preferably 0.2 to 7 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the starch. Within such a range, the effects of the present invention are remarkable. In one embodiment, the content of the starch lubricant is 0.1 to 3 parts by weight relative to 100 parts by weight of the starch.
[0034] (Surfactant) The surfactant is a compound composed of a hydrophobic group and a hydrophilic group, and the hydrophilic / hydrophobic balance can be controlled by adjusting the degree of esterification of the surfactant compound, the type of fatty acid (presence or absence of a hydroxyl group, saturated or unsaturated fatty acid, alkyl chain length), and the degree of polymerization. The surfactant not only has the effect of improving the granulation property of the starch granule of the present invention (examples include improvement of the production rate per hour of the starch granule, improvement of hardness, improvement of uniformity, and improvement of the cleanability of the granulation equipment, etc.), but also has the effect of imparting dispersibility, fluidity improvement, plasticization, lubricity, etc. to starch when the starch granule is mixed with a thermoplastic resin to obtain a starch-containing resin composition. Among the effects of the surfactant, the improvement in granulation property is due to the fact that the generation of frictional heat generated during starch granulation can be reduced and the gelatinization of starch can be suppressed in order to impart lubricity in the production of the starch granule, and this is a surprising effect achieved by the present invention.
[0035] The surfactant may be an emulsifier (eg, an emulsifier used as a food additive).
[0036] In one embodiment, the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerin fatty acid esters, and alcohol esters of condensed hydroxy fatty acids.
[0037] The polyhydric alcohol fatty acid ester is an ester compound composed of a polyhydric alcohol and a fatty acid.
[0038] Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin, polyalkane polyols which are polymers of the alkane polyols, sugars such as sucrose, and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more.
[0039] Any appropriate fatty acid may be used as the fatty acid constituting the polyhydric alcohol fatty acid ester. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms) is used. Specific examples of the fatty acid include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, and hydrogenated castor oil fatty acid (a fatty acid containing small amounts of stearic acid and palmitic acid in addition to 12-hydroxystearic acid). Palmitic acid and stearic acid are particularly preferred. The fatty acids may be used alone or in combination of two or more.
[0040] The polyhydric alcohol fatty acid ester can be obtained by esterification reaction of the polyhydric alcohol with a fatty acid. Specific examples of the polyhydric alcohol fatty acid ester include glycerin mono fatty acid ester, glycerin di fatty acid ester, fats and oils (coconut oil, palm oil, soybean oil, castor oil, etc.), hardened oils (hardened coconut oil, palm super hardened oil, etc.), sorbitan fatty acid ester, propylene glycol fatty acid ester, polyoxyethylene sorbitan fatty acid ester, sucrose fatty acid ester, glycerin diacetate monolaurate, diglycerin stearate, glycerin acetate fatty acid ester, glycerin lactate fatty acid ester, glycerin diacetyl tartaric acid fatty acid ester, etc., which are used as food emulsifiers. The polyhydric alcohol fatty acid ester may be used alone or in combination of two or more.
[0041] The polyglycerol fatty acid ester is an ester compound composed of polyglycerol and a fatty acid.
[0042] As the polyglycerin, any suitable polyglycerin can be used.Specific examples of the polyglycerin include diglycerin, triglycerin, tetraglycerin, pentaglycerin, hexaglycerin, heptaglycerin, octaglycerin, nonaglycerin, decaglycerin, eicosaglycerin, and tetracontaglycerin.Of these, diglycerin, triglycerin, pentaglycerin, or decaglycerin is preferred.Polyglycerin may be used alone or in combination of two or more.
[0043] Any appropriate fatty acid may be used as the fatty acid constituting the polyglycerol fatty acid ester. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms) is used. Specific examples of the fatty acid include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, and hydrogenated castor oil fatty acid (a fatty acid containing small amounts of stearic acid and palmitic acid in addition to 12-hydroxystearic acid). Palmitic acid and stearic acid are particularly preferred. The fatty acids may be used alone or in combination of two or more.
[0044] Specific examples of the polyglycerol fatty acid ester include diglycerol palmitate, diglycerol stearate, diglycerol oleate, decaglycerol palmitate, decaglycerol stearate, decaglycerol oleate, etc. These may be used alone or in combination of two or more.
[0045] The fatty acid esterification rate of the polyglycerol fatty acid ester is preferably 35% or more, more preferably 50% to 70%. Within this range, a starch granule having excellent production stability can be obtained. In addition, the starch granule has excellent dispersibility in resins (especially thermoplastic resins). The esterification rate (%) is expressed by the formula: esterification rate (%) = (mol number of constituent fatty acids / number of hydroxyl groups of polyglycerol) x 100.
[0046] The polyglycerol fatty acid ester can be obtained by any suitable method. For example, it can be obtained by reacting polyglycerol with a fatty acid in the presence or absence of a catalyst (e.g., phosphoric acid, p-toluenesulfonic acid, caustic soda) at 100°C to 300°C (preferably 120°C to 260°C) while removing the generated water from the system. The reaction is preferably carried out in the presence of an inert gas. It may also be carried out in an azeotropic solvent such as toluene or xylene.
[0047] The alcohol ester of the condensed hydroxy fatty acid can be obtained by esterification reaction of the condensed hydroxy fatty acid with alcohol. The alcohol ester of the condensed hydroxy fatty acid can be obtained, for example, by mixing the condensed hydroxy fatty acid with alcohol, adding an alkali catalyst such as caustic soda or an acid catalyst such as phosphoric acid to the resulting mixture, and removing reaction water under heating. The progress of esterification during this reaction can be confirmed by measuring the acid value, saponification value, hydroxyl value, etc. Here, the condensed hydroxy fatty acid is a compound that can be obtained by dehydration condensation of hydroxy fatty acid. The condensed hydroxy fatty acid can be obtained, for example, by adding an alkali catalyst such as caustic soda to hydroxy fatty acid, and removing reaction water under heating to perform dehydration condensation.
[0048] The condensed hydroxy fatty acid is a condensation product of a hydroxy fatty acid, and the degree of condensation is preferably not less than 2, more preferably not less than 4. The upper limit of the degree of condensation of the condensed hydroxy fatty acid is, for example, 20. The degree of condensation can be calculated from the acid value of the raw hydroxy fatty acid and the acid value after the condensation reaction.
[0049] The above-mentioned hydroxy fatty acid is a fatty acid having one or more hydroxyl groups in the molecule.Specific examples of hydroxy fatty acid include ricinoleic acid, 12-hydroxystearic acid, savinic acid, 2-hydroxytetradecanoic acid, iprolic acid, 2-hydroxyhexadecanoic acid, yarapinolic acid, uniperilic acid, ambrettolic acid, aluritic acid, 2-hydroxyoctadecanoic acid, 18-hydroxyoctadecanoic acid, 9,10-dihydroxyoctadecanoic acid, camrolenoic acid, ferronic acid, and cerebronic acid.Hydroxy fatty acid may be used alone or in combination of two or more.
[0050] Examples of the alcohol include monohydric alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; dihydric alcohols such as ethylene glycol and propylene glycol. In addition, polyhydric alcohols may be used as the alcohol. Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin; polyalkane polyols which are polymers of the alkane polyols; sugars such as sucrose; and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more.
[0051] Specific examples of the alcohol ester of the condensed hydroxy fatty acid include condensed ricinoleic acid hexaglycerin ester, which is an ester of condensed ricinoleic acid and hexaglycerin of glycerin 6 polymer, condensed ricinoleic acid tetraglycerin ester, which is an ester of condensed ricinoleic acid and tetraglycerin of glycerin 4 polymer, condensed 12-hydroxystearic acid propylene glycol ester, which is an ester of condensed 12-hydroxystearic acid and propylene glycol, and condensed linoleic acid propylene glycol ester, which is an ester of condensed ricinoleic acid and propylene glycol, etc. These may be used alone or in combination of two or more.
[0052] The alcohol ester of the condensed hydroxy may be a commercially available product. Examples of the commercially available product include "Tirabazole P-4", "Tirabazole VR-01", "Tirabazole VR-08", and "Tirabazole H-818" manufactured by Taiyo Kagaku Co., Ltd.
[0053] The content of the surfactant is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 7 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of starch. If the content is within such a range, the above-mentioned effects of the present invention become prominent.
[0054] (Starch plasticizer) A starch plasticizer refers to a compound that is incorporated into the molecular structure of starch, compatibilizes it, and provides the effect of imparting flexibility, fluidity, etc. In this specification, water is not considered to be a starch plasticizer.
[0055] Specific examples of the starch plasticizer include high-boiling alcohols such as n-octyl alcohol, isodecyl alcohol, and n-decyl alcohol, polyhydric alcohols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, propanediol, 1,3-butanediol, glycerin, diglycerin, trimethylolpropane, pentaerythritol, 3-methyl-1,3,5-pentatriol, and sorbitol, and polyalkylene oxides such as polyethylene glycol, polypropylene glycol, polyglycerin, and ethylene glycol-propylene glycol copolymers. In one embodiment, the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin, and sorbitol.
[0056] Another example of the starch plasticizer is low molecular weight aliphatic polyester. Examples of low molecular weight aliphatic polyester include polycondensates of diols such as ethylene glycol and butylene glycol with dicarboxylic acids such as adipic acid and succinic acid; and hydroxyalkanoates made of low polymers such as caprolactone, lactic acid, and hydroxybutyric acid. Among them, low molecular weight aliphatic polyesters formed by esterifying terminal carboxylic acids with alcohols having 2 to 8 carbon atoms are preferably used.
[0057] The content of the starch plasticizer is preferably 0.1 to 10 parts by weight, more preferably 0.3 to 5 parts by weight, and further preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of starch. Within such a range, a starch granule capable of forming a resin composition having excellent starch dispersibility and resin melt flowability can be obtained.
[0058] A-5 Other ingredients The starch granules of the present invention may further contain any appropriate other components (additives) as necessary. Examples of additives include antioxidants, light stabilizers, foaming agents, UV absorbers, foaming agents, antiblocking agents, heat stabilizers, impact modifiers, antibacterial agents, compatibilizers, plasticizers, tackifiers, processing aids, lubricants, coupling agents, flame retardants, oxygen scavengers, colorants, etc. The additives may be added in the form of liquid, powder, pellets, granules, or in the form of a masterbatch, etc., during granulation of the starch granules or in the resin compounding process.
[0059] In one embodiment, the additives can be incorporated into the starch granules during granulation in a semi-wet granulator.
[0060] In one embodiment, the starch granules contain trehalose. By adding trehalose, the hardness of the starch granules can be improved and deterioration of starch in the starch-containing resin composition over time can be suppressed.
[0061] B. Manufacturing method of starch granules The starch granules can be produced by any suitable method. The starch granules can be obtained, for example, by subjecting a mixture containing the starch, the water-soluble polysaccharide, and the starch lubricant to a semi-wet granulation method. In one embodiment, the method for producing the starch granules includes a mixing step of mixing the starch, the water-soluble polysaccharide, and the starch lubricant, and a granulation step of obtaining a granule from the mixture obtained through the mixing step. In the mixing step, water may be further mixed. The starch, the water-soluble polysaccharide, and the starch lubricant described in Section A can be used.
[0062] The water to be added is not particularly limited, and for example, tap water, distilled water, ion-exchanged water, hard water, soft water, etc. can be used.
[0063] In the above mixing step, the amount of water to be added is usually 1 to 30 parts by weight, preferably 2 to 20 parts by weight, and more preferably 3 to 17 parts by weight, relative to 100 parts by weight of starch. Note that, although the starch powder used as a raw material in the starch granules of the present invention may contain a certain amount of moisture, the above amount of water is the number of parts added excluding the amount of moisture contained in the raw starch powder.
[0064] In one embodiment, the amount of water in the mixing step is adjusted according to the amount of the water-soluble polysaccharide, for example, 1 to 30 parts by weight, preferably 3 to 25 parts by weight, and more preferably 5 to 20 parts by weight, per 1 part by weight of the water-soluble polysaccharide.
[0065] In one embodiment, in the mixing step, powdery raw materials (starch, water-soluble polysaccharides, starch lubricant (surfactant and / or starch plasticizer), and other additives) are mixed to obtain a powder mixture; liquid raw materials (water, starch lubricant (surfactant or starch plasticizer)) are mixed separately to obtain a mixed liquid (which may be a suspension dispersion); and then the mixed liquid is gradually mixed into the powder mixture. In this way, the mixing time can be shortened. For example, the water-soluble polysaccharides can be mixed as an aqueous solution in which they are dissolved in water in advance, but the solution viscosity of the polysaccharide aqueous solution becomes too high, so it becomes necessary to extend the mixing time.
[0066] The mixture obtained in the above mixing step exhibits sufficient and highly homogeneous binding strength as a binder because the water-soluble polysaccharide can uniformly cover the surface of the starch particles over a wide area, which significantly improves the granulation property and productivity of the starch granules, and allows the obtained granules to exhibit appropriate hardness (shape retention) and reduce fine powder.
[0067] In the mixing step, it is preferable to mix the components at room temperature and homogenize them using any suitable mixer, such as a Henschel mixer, a powder kneader (KDH, KDA, CKD, CPM) (Dalton), a Spartan mixer (SPM) (Dalton), or a SP granulator (SPG) (Dalton).
[0068] The mixing time in the mixing step can be any appropriate time depending on the type of components, the type of mixer, the component blending ratio, etc. Preferably, the mixing time is set so that the surface of the starch is sufficiently and uniformly covered with the aqueous polysaccharide solution. With a high-speed mixer such as a Henschel mixer or a Spartan mixer, the mixing can be carried out within a processing time of 1 to 10 minutes. On the other hand, with a powder kneader, a processing time of several minutes to 60 minutes may be required.
[0069] In the granulation step, a compression granulation method is preferably used. In addition, in the granulation step, a semi-wet granulation method can be preferably used. Examples of the compression granulation method / semi-wet granulation method include a disk pelleter method, a double granulation method, and a briquetting method. From the viewpoint of the balance between productivity and the quality of the obtained starch granules, the disk pelleter method is preferably used.
[0070] The basic structure of the disk pelletizer is one or two disks with many holes of 2mm to 30mm, and a roller for pressure-feeding the raw material into the holes of the disk. The raw material supplied between the disk and the roller, or between two disks, is pressed into the holes of the disk as the roller rotates, and a cylindrical extrudate is formed. Here, the disk holes are tapered, and a compressive stress is applied from the outer periphery of the die hole in the process of the starch mixture passing through the holes. The length of this tapered hole is called the effective length. The extruded granule precursor is cut by a cutter or the like on the back side of the disk to obtain a pellet-shaped starch granule. The length of the granule can be adjusted by the distance between the back side of the disk and the cutter and the number of rotations of the roller. More specifically, the disc pelleter type includes a roller disc die type, a roller ring die type, a double die type, a flat die type, etc. An example of a commercially available disc pelleter type granulator is the Disc Pelletter F Series manufactured by Dalton.
[0071] Although disk pelletizers do not usually have a heating / cooling system, they do heat up due to shear heat generated during operation. In the granulation process, if the temperature during granulation reaches the gelatinization temperature of starch (approximately 70°C or higher), starch may gelatinize, making granulation difficult. In order to prevent starch from gelatinizing due to shear heat generated during granulation, it is preferable to cool the disk pelletizer by installing a cooling jacket as necessary, and it is preferable to control the granulation temperature to preferably 60°C or less, more preferably 55°C or less, and even more preferably 50°C or less.
[0072] In the granulation step, the granules (or granule precursor) may be dried as necessary to optimize the moisture content. Any appropriate method can be used as the drying method. In addition, a process such as a vibrating sieve can be carried out before or after drying the granules to obtain starch granules from which fine powder has been removed. Any appropriate drying equipment can be used for drying. For example, a vibrating fluidized dryer is preferred because it can perform drying efficiently in a short time, and examples of such devices include the VDF series vibrating fluidized dryers manufactured by Dalton.
[0073] C. Melt compounding of resin and starch granules In one embodiment, there is provided a melt compound of the starch granules and a resin, which is preferably a thermoplastic resin.
[0074] The above-mentioned thermoplastic resin is not particularly limited, but since kneading with a resin at high temperatures causes deterioration of starch, it is preferable to use a thermoplastic resin whose processable temperature is 200°C or less, preferably 180°C or less.
[0075] Specific examples of the thermoplastic resin include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), polypropylene (PP), polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polystyrene (PS), high impact polystyrene (HIPS), styrene-butadiene copolymer, styrene-butadiene elastomer (SBS), hydrogenated styrene-butadiene elastomer (SEBS), styrene-isoprene elastomer (SIS), hydrogenated styrene-isoprene elastomer (SEPS), polyolefin elastomer (TPO), polyvinyl acetate (PVAc), ABS resin (acrylonitrile butadiene styrene resin), AS resin, acrylic resin (PMMA), etc.
[0076] In addition, a biodegradable resin may be used as the resin. Examples of the biodegradable resin include aliphatic polyester resins (e.g., homopolymers or copolymers of polycaprolactone, polylactic acid, polyethylene succinate, polybutylene succinate-adipate, polyhydroxyvalerate, etc., and modified homopolymers or copolymers thereof), aliphatic / aromatic polyester resins (e.g., block polymers or random polymers of aliphatic carboxylic acids or hydroxy acids, aromatic dicarboxylic acids and 1,3-propanediol, etc.), and polyvinyl alcohol resins (e.g., polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, ethylene-vinyl alcohol copolymers, etc.). Examples of naturally derived biodegradable resins include natural rubber. By using the starch granules in a biodegradable resin and blending starch, the mechanical properties, bio content, and biodegradation rate of the resin can be adjusted according to the application, and the resin can be used alone or in combination of two or more kinds, or in combination with an olefin resin.
[0077] The blending ratio of the thermoplastic resins may be any appropriate blending ratio depending on the desired properties and applications.
[0078] Any suitable method can be used as a method for producing the molten compound. For example, a kneader, a Banbury mixer, a roll, a single-screw extruder or a multi-screw extruder having two or more screws can be used. A twin-screw extruder is preferably used. The melt-kneaded composition is pelletized.
[0079] In the melt compounding, the starch granules are melt-kneaded with a resin usually at a temperature range of 80° C. to 170° C., preferably 100° C. to 160° C., to produce a starch-containing resin composition. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, parts and percentages are based on weight unless otherwise specified.
[0081] [Example 1] A powder kneader (manufactured by Dalton, product name "KDHJ-10"; processing capacity: 6 L) was charged with 100 parts by weight of starch (Sanwa Starch Industry Co., Ltd., raw starch made from corn, product name "Corn Starch Y"; in the table, "A-1"), 1 part by weight of pullulan, a water-soluble polysaccharide (manufactured by Hayashibara Co., Ltd., in the table, "B-1"), and 1 part by weight of trehalose (manufactured by Hayashibara Co., Ltd., in the table, "E-1") as an additional component, and the mixture was stirred for 6 minutes while rotating the stirring blade at a rotation speed of 30 rpm, to obtain powder mixture A. Separately, 13 parts of water, 1 part by weight of polyglycerol condensed hydroxy fatty acid ester (manufactured by Taiyo Kagaku Co., Ltd., product name "Chirabazol H818"; "C-1" in the table) as a surfactant, and 1 part by weight of glycerin as a starch plasticizer were weighed into a 1 L plastic container and thoroughly stirred at room temperature to obtain aqueous dispersion mixture B. Water-dispersed mixture B was gradually added to powder mixture A in a powder kneader while stirring with a stirring blade at a rotation speed of 30 rpm. After the entire amount of water-dispersed mixture B was mixed, stirring was continued for an additional 6 minutes to obtain a mixture of powder mixture A and water-dispersed mixture B (mixture C). Mixture C was put into a disk pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175; capacity: 5 L") to obtain a pelleted starch granule. At this time, the die hole diameter was set to 3 mmφ, the die plate thickness was set to 15 mm, the effective length of the die hole was set to 10 mm, and the rotation speed of the roller of the dispelleter was set to 108 rpm to obtain a starch granule (MB-1). The temperature of the obtained starch granules (MB-1) immediately after granulation was measured with a contact thermocouple and found to be 55° C. In addition, the moisture content was measured and found to be 23.4% by weight.
[0082] [Examples 2 to 9, Comparative Examples 1 to 10] Starch granules MB-2 to MB-9 and MB-C1 to MB-C10 were obtained in the same manner as in Example 1, except that the starch, water-soluble polysaccharide, starch lubricant (surfactant and / or starch plasticizer), and other components shown in Table 1 were used in the amounts shown in Table 1 (units in the table: parts by weight). The specific contents of each component used in Examples 1 to 9 and Comparative Examples 1 to 10 are as shown in Table 2.
[0083] [Table 1]
[0084] [Table 2]
[0085] <Evaluation> The filler granules obtained in Examples 1 to 9 and Comparative Examples 1 to 10 were subjected to the following evaluations. The results are shown in Table 3. Also, a photograph of the appearance of the starch granule (MB-1) is shown in FIG. (1) Granulation property The obtained filler granules were checked, and the granulation properties were evaluated according to the following criteria. ○: Granules with a diameter of 3 mm are obtained. △: The product takes the form of starch granules, but the binding strength is insufficient and the product easily falls apart. ×: The starch clogs the die or the starch has no binding properties and does not form granules. (2) Granulation speed The production rate of starch granules per hour (kg / Hr) was calculated. (3) Granule temperature The temperature (unit: °C) of the starch granules immediately after granulation was measured using a contact thermocouple. (4) Collapse strength The disintegration stress (unit: kg) of the starch granules was measured using a Kiya hardness tester (manufactured by Shiro Sangyo Co., Ltd., product name "WPF1600-B") The measured value was the average value of 20 starch granules. (5) Amount of fine powder 1 kg of the starch granules was weighed out and sieved through a 14 mesh sieve to measure the mass proportion of fine powder (unit: weight %). (6) Bulk density The starch granules were weighed out in a 1-liter measure to a volume of exactly 1 liter, and the weight was measured to calculate the bulk density (unit: kg / L) of the starch granules. (7) Pellet size Twenty grains of starch granules were taken out, and the average length and diameter of the granules were measured using a caliper. (8) Moisture content The amount of moisture (unit: weight %) remaining in the starch granules was measured using an infrared moisture meter (FD-660, manufactured by Kett Electric Laboratory).
[0086] [Table 3]
[0087] As shown in Table 3, with MB-1 to MB-9, it was possible to obtain starch granules in the form of pellets with stable pellet shape, high granulation speed, and appropriate hardness. On the other hand, with MB-C1 to MB-C10, starch granules were not obtained or the starch granules had low disintegration strength. MB-C1 to MB-C3 and MB-C5 are examples in which no starch lubricant was added, but the heat generated during granulation caused the gelatinization of the starch to progress, causing the starch to clog the die.
[0088] [Example 10] 60 parts by weight of PBAT resin (manufactured by BASF, product name "Ecoflex F Blend C1200", MFR 3.8g / 10min) and 40 parts by weight of starch granules (MB-1) were charged into a twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., product name "TEM37SS", L / D=48) and continuously melt-kneaded to produce pellets of a starch-containing resin composition. The PBAT resin and the starch granules MB-1 were each independently quantitatively fed into the twin-screw extruder at the hopper position at the most upstream part of the extruder via a gravimetric feeder. The cylinder temperatures of the extruder were set to 140°C in the front stage, 120°C in the middle stage, and 140°C in the rear stage. The settings of the twin-screw extruder (discharge speed, main screw rotation speed) are as shown in Table 4. The melt-kneaded resin composition was extruded in the form of a strand, cooled in a water-cooled bath, and formed into pellets having a length of about 3 mm.
[0089] [Example 11] Pellets of a starch-containing resin composition were produced in the same manner as in Example 10, except that a liquid addition nozzle was attached to the middle stage of the extruder and 5 parts of water per 100 parts by weight of the PBAT resin and starch granules combined was injected using a gear pump.
[0090] [Example 12] Pellets of a starch-containing resin composition were produced in the same manner as in Example 10, except that the discharge rate was 20 kg / h, the front stage of the extruder was 120°C, and the rotation speed of the main screw was 200 rpm.
[0091] [Example 13] Pellets of a starch-containing resin composition were produced in the same manner as in Example 12, except that the discharge rate was 30 kg / h.
[0092] [Comparative Example 11] Pellets of a starch-containing resin composition were produced in the same manner as in Example 11, except that starch powder A-1 was used instead of starch granules MB-1.
[0093] [Comparative Example 12] Except for changing the discharge rate to 30 kg / h, an attempt was made to produce pellets of a starch-containing resin composition in the same manner as in Comparative Example 11. The starch powder A-1 did not bite into the raw material inlet properly, and pellets could not be obtained stably. Comparing Example 13 with Comparative Example 12, it can be seen that the use of starch granules MB-1 eliminates the feed neck of starch powder A-1, enabling high productivity and at the same time enabling a melt compound that simultaneously satisfies good dispersibility of starch in the resin.
[0094] <Evaluation> The pellets of the thermoplastic resin compositions obtained in Examples 10 to 13 and Comparative Example 11 were subjected to the following evaluations. The results are shown in Table 4. (a) Resin composition discharge speed (unit: kg / Hr) It is the amount of compound resin composition discharged per hour. (b) Extruder load (unit: %) This is the displayed value of the actual measured power load percentage (percentage of the maximum allowable motor load) of a twin screw extruder or single screw extruder. (c) Temperature of molten resin at the die (unit: °C) The temperature of the resin composition extruded from the die was measured with a contact thermocouple. (d) Dispersibility of starch in resin composition The resin composition pellets were rolled by a hot press to form a sheet with a thickness of about 0.5 mm. The remaining starch aggregates were visually observed through the sheet and evaluated according to the following criteria. A photograph of the appearance of the sheet in Example 10 is shown in FIG. 2. AA: Good dispersion state with almost no starch agglomerates observed A: A state in which a small amount of relatively small starch aggregates remain. BB: A state in which a considerable number of relatively small starch aggregates remain B: Starch aggregates are large (Distribution order: AA>A>BB>B (left good)) (e) MFR in resin composition (unit: g / 10 min) The MFR of the resin composition pellets was measured at 190° C. under a load of 5 kg (in accordance with ISO 1133).
[0095] [Table 4]
[0096] As is clear from Table 4, according to the present invention, a resin composition having excellent dispersibility of starch despite containing a high concentration of starch can be obtained with high productivity. Furthermore, a comparison of MFR between Example 11 and Comparative Example 11 shows that the starch-containing resin composition obtained by using the starch granules of the present invention has high fluidity and excellent processability.
Claims
1. The present invention relates to a starch-based emulsion, and the starch lubricant is at least one selected from the group consisting of surfactants and starch plasticizers; The content of the water-soluble polysaccharide is 0.1 to 5 parts by weight based on 100 parts by weight of the starch, The content of the starch lubricant is 0.1 to 5 parts by weight based on 100 parts by weight of starch, The moisture content is 1% by weight to 30% by weight. Starch granules for resin molding.
2. The content of the water-soluble polysaccharide is 0.1 to 3 parts by weight based on 100 parts by weight of starch, The content of the starch lubricant is 0.1 to 3 parts by weight based on 100 parts by weight of starch. The starch granule according to claim 1.
3. 3. The starch granule according to claim 1, wherein the water-soluble polysaccharide is at least one selected from the group consisting of pullulan and dextrin.
4. 4. The starch granule according to claim 1, wherein the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerol fatty acid esters and alcohol esters of condensed hydroxy fatty acids.
5. 5. The starch granule according to claim 1, wherein the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin and sorbitol.
6. The starch granule according to any one of claims 1 to 5, wherein the starch is a pregelatinized starch.
7. A mixing step of mixing starch, a water-soluble polysaccharide, and a starch lubricant; A granulation step of granulating the mixture obtained through the mixing step, The mixing step further comprises mixing water, The amount of water is 5 to 20 parts by weight per 1 part by weight of the water-soluble polysaccharide. A method for producing starch granules.
8. The method for producing a starch granule according to claim 7, wherein the granulation step comprises granulation by a semi-wet granulation method.
9. The method for producing a starch granule according to claim 7 or 8, wherein the granulation step comprises granulation by a disk pelleter method.
Citation Information
Patent Citations
Material on basis of starch flour
JP1994234882A
Material based on starch
JP1995070205A
Resin composition
JP2009120651A
Biodegradable resin composition and molded article obtained by molding the composition
JP2012031330A
Production method of granular soup containing starch
JP2015171352A
